Eudesis tenuissima sp. n. on Italian Peninsula (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Eudesis Reitter is a Mediterranean endogean endemic genus comprising four species known to occur on Sardinia, and one in the coastal region of Spain. The first species found in continental Italy is described, Eudesis tenuissima sp. n., and compared with remaining members of the genus.